2008
DOI: 10.1007/s10620-008-0370-3
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the Dorsal Pancreas and Associated Diseases

Abstract: Difficulties involved in obtaining a firm diagnosis have led to a variety of terms being used to describe this congenital disease. Diagnosis of agenesis of the dorsal pancreas is inconclusive without demonstration of the absence of the dorsal pancreatic duct. Here we describe the embryological development of the pancreas, the so-far known cases of agenesis of the dorsal pancreas with associated medical problems, and the diagnostic measures to find the right conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 54 publications
4
82
0
Order By: Relevance
“…Moreover, the association of congenital heart defects such as septal defects, tetralogy of Fallot or pulmonary artery stenosis is common [4]. Although few cases of agenesis of the dorsal pancreas describe features similar to our patient, the individual symptoms may vary from case to case [1]. Most cases describe single, but not familiar, patients.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Moreover, the association of congenital heart defects such as septal defects, tetralogy of Fallot or pulmonary artery stenosis is common [4]. Although few cases of agenesis of the dorsal pancreas describe features similar to our patient, the individual symptoms may vary from case to case [1]. Most cases describe single, but not familiar, patients.…”
Section: Discussionmentioning
confidence: 65%
“…Pancreas divisum is the most common anomaly. However, agenesis of the dorsal pancreas, with the absence of the pancreatic body and tail is very rare; only 53 cases have been described in medical literature in the last 100 years [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This anomaly was first described in 1911, and 53 cases were reported up to 2008 (3,4). Several authors have reported an association between DPA and acinar-ductal metaplasia (ADM), and neoplasia of the remnant pancreas (ventral pancreas) and diabetes (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%